Application of material of extra-large tonnage and large size 840 kn suspension porcelain insulator and preparation method thereof

CN122977823APending Publication Date: 2026-10-27PINGXIANG XINYUAN INSULATOR GRP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611434221.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-16
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

整件采用高刚玉或高氧化锆含量材料,虽然能够提高强度,但会增加薄伞区干燥开裂、烧成变形及材料成本;整件采用较低刚玉含量材料,又难以满足头部抗裂和疲劳性能要求

Benefits of technology

本发明将含3Y-ZrO2、MgAl2O4尖晶石晶种及双峰α-Al2O3的高韧性瓷料配置在头部和伞根高应力区域,同时在绝缘伞区采用更易成型且介电性能较好的瓷料,实现材料性能与受力部位相匹配;连续过渡区消除了突变式材料接合面,并通过烧成线收缩率和平均线膨胀系数的双重匹配,降低了大规格瓷件在干燥、烧成及交变载荷作用下发生界面开裂的风险;共轴真空挤制工艺能够与现有盘形悬式瓷绝缘子旋坯生产线衔接,有利于稳定控制梯度位置和产品尺寸,适合840 kN大规格瓷绝缘子的批量制造。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application provides application of a material of an extra-large-tonnage large-size 840 kN suspension type porcelain insulator and a preparation method thereof, and relates to the technical field of high-strength electric porcelain materials.The material forms a bearing core area, a continuous transition area and an insulating umbrella area in the same porcelain piece; the bearing core area is synergistically toughened by double-peak alpha-Al2O3, 3Y-ZrO2 and MgAl2O4 spinel, the insulating umbrella area adopts a lower corundum content and introduces mullite seeds, and the composition of the continuous transition area changes in a ladder type along a radial direction; by controlling the drying linear shrinkage difference, the sintering linear shrinkage difference and the average linear expansion coefficient difference between the areas, and by adopting coaxial vacuum extrusion, humidity gradient drying and small temperature difference sintering, integral co-sintering without macroscopic interfaces is realized.The obtained porcelain piece has high toughness of the head part, high dielectric strength of the umbrella area and large-size size stability, and is suitable for extra-high voltage AC and DC suspension type porcelain insulators with a specified electromechanical breakdown load of 840 kN.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-strength electrical porcelain materials technology, and in particular to the application and preparation method of an extra-large tonnage, large-specification 840 kN suspension porcelain insulator material. Background Technology

[0002] As ultra-high voltage power transmission projects develop towards longer spans, heavy icing, and large-section multi-split conductors, tension insulator strings need to withstand higher static tensile loads and long-term alternating loads. When the specified electromechanical failure load of disc suspension porcelain insulators increases to 840 kN, problems such as stress concentration at the porcelain head, moisture gradient of large-size blanks, and firing temperature differences become more prominent.

[0003] Existing high-strength electrical porcelain typically employs a single, uniformly composed piece of alumina or zirconia-toughened porcelain. While using high-corundum or high-zirconia content materials can improve strength, it increases the risk of drying cracking, firing deformation, and material costs in the thin-umbrella area. Conversely, using materials with lower corundum content makes it difficult to meet the requirements for crack resistance and fatigue performance at the head. Existing solutions that improve load-bearing capacity through steel caps, steel feet, or adhesive materials also fail to address the issue of material property configuration in different areas within the porcelain component.

[0004] Therefore, there is a need to provide a functional partition material and its preparation method suitable for 840 kN suspension porcelain insulators, so as to take into account the load-bearing capacity of the head, the dielectric properties of the umbrella area and the manufacturing stability of large-size porcelain parts. Summary of the Invention

[0005] The first aspect of this invention provides an extra-large tonnage, large-specification 840 kN suspension porcelain insulator. The porcelain component of the suspension porcelain insulator is a single, dense porcelain component formed by co-firing a load-bearing core area, a continuous transition area, and an insulating umbrella area. Taking the central axis of the porcelain component as a reference, the load-bearing core area is located at the central head and inside the umbrella root of the porcelain component, and the insulating umbrella area is located radially outside the continuous transition area. The continuous transition area is located between the load-bearing core area and the insulating umbrella area. The raw material systems of the load-bearing core area, the continuous transition area, and the insulating umbrella area do not contain pore-forming agents. The core material, by weight, comprises the following: 47-51 parts α-Al₂O₃, 18-21 parts calcined kaolin, 15-18 parts plastic kaolin, 8-11 parts potassium feldspar, and 5-8 parts sodium feldspar; each 100 parts of the core material further comprises 1.2-2.0 parts 3Y-ZrO₂, 0.7-1.3 parts MgAl₂O₄ spinel seed crystals, 0.25-0.55 parts talc, and 0.15-0.35 parts TiO₂. The 3Y-ZrO₂ refers to ZrO₂ stabilized with 3 mol% Y₂O₃. The low addition amount of 3Y-ZrO₂ is mainly distributed in the core area, undergoing a controlled phase transformation under the stress field at the crack tip and absorbing crack propagation energy; the MgAl₂O₄ spinel seed crystals inhibit the abnormal growth of local corundum and utilize the thermal expansion difference with corundum and the glass phase to form compressive stress in the micro-region. Bimodal α-Al2O3 takes into account both the particle skeleton and sintering gap filling, thus achieving high load-bearing toughness without using more than 11wt% homogeneous zirconium oxide. The insulating umbrella region base material, by weight, comprises the following: 37-41 parts α-Al₂O₃, 21-25 parts calcined kaolin, 18-22 parts plastic kaolin, 10-13 parts potassium feldspar, and 5-8 parts sodium feldspar; each 100 parts of the insulating umbrella region base material further comprises 0.15-0.45 parts 3Y-ZrO₂, 1.0-1.8 parts mullite seed crystals, 0.20-0.50 parts talc, and 0.10-0.30 parts TiO₂. By reducing the amount of corundum and 3Y-ZrO₂ and increasing the proportion of plastic components and mullite seed crystals, the insulating umbrella region improves the integrity of the spinning blank, dielectric uniformity, and resistance to cold and heat in the large-diameter thin umbrella region. The continuous transition zone is formed by the raw material system of the bearing core zone and the raw material system of the insulating umbrella zone with a dry basis mass ratio that changes in a stepwise manner along the radial direction. The dry basis mass ratio changes in a stepwise manner from 90:10 to 75:25 near the bearing core zone to 25:75 to 10:90 near the insulating umbrella zone. The continuous transition zone does not bond the two finished ceramic pieces together, but allows the two plastic clay materials to diffuse and continuously mix in the clay segment state. After one firing, the crystalline phase and the glass phase transition continuously. The difference in linear shrinkage between the load-bearing core area and the insulating umbrella area under the same firing regime is ≤0.25%, and the difference in the average linear expansion coefficient between 25~600℃ is ≤0.35×10⁻⁶. -6 K -1 The above matching was achieved by adjusting the feldspar ratio, α-Al2O3 particle size distribution, and kaolin ratio within the given range for each zone.

[0006] Preferably, the radial boundary radius of the bearing core region in the finished ceramic part is 88~100 mm, and the radial width of the continuous transition zone is 8~16 mm. Using the radial variation of 3Y-ZrO2 content as a characterization, the radial polished section of the finished ceramic part is scanned by SEM-EDS in the continuous transition zone to obtain Zr element line scans. An analysis position is set every 1 mm along the radial direction, and three fields of view are tested at each position. The 3Y-ZrO2 content is calculated according to the calibration curve. The variation of 3Y-ZrO2 content between adjacent analysis positions is ≤0.18 wt% to exclude abrupt two-layer structures that form local weak surfaces.

[0007] Preferably, the α-Al₂O₃ in the supporting core region is composed of fine-grained α-Al₂O₃ and coarse-grained α-Al₂O₃, wherein the fine-grained α-Al₂O₃ has a D₂O₃ content of 100%. 50 The Do of the coarse-grained α-Al2O3 is 0.8~1.6 μm. 50 The particle size is 5.0~8.0 μm, and the dry basis mass ratio of the two is 65:35~78:22; the D of the 3Y-ZrO2 50 The diameter is 0.25~0.60 μm; the D of the MgAl2O4 spinel seed crystal is... 50 The range is 0.8~2.0μm.

[0008] Preferably, after firing, the bearing core region comprises 38-48 vol% corundum phase, 16-24 vol% mullite phase, 0.8-1.6 vol% tetragonal ZrO2 phase, and 22-32 vol% glass phase, and the insulating umbrella region comprises 28-38 vol% corundum phase, 18-28 vol% mullite phase, and 28-38 vol% glass phase; the apparent porosity of both the bearing core region and the insulating umbrella region is ≤0.8%, and the total porosity is ≤2.5%.

[0009] Preferably, the room temperature three-point bending strength of the load-bearing core region is ≥290 MPa, and the fracture toughness is ≥4.0 MPa·m. 1 / 2 The power frequency breakdown field strength of the insulating umbrella region is ≥30 kV / mm, and the volume resistivity is ≥1.0×10⁻⁶. 13 Ω·m; the shear strength of the continuous transition zone is ≥55 MPa.

[0010] Preferably, the porcelain head of the suspension porcelain insulator has a height of 100-112 mm, an outer diameter of 120-132 mm, an inner diameter of 74-84 mm, a maximum umbrella diameter of 410-425 mm, a structural height of 295-305 mm, and a nominal creepage distance of 650-700 mm; the porcelain part, together with the steel cap and steel foot, forms a disc-shaped suspension porcelain insulator with a specified electromechanical breaking load of 840 kN.

[0011] The second aspect of this invention provides a method for preparing the aforementioned extra-large tonnage, large-specification 840 kN suspension porcelain insulator, comprising the following steps: S1. Prepare the slurry for the core area and the insulating umbrella area separately, ensuring that the difference in moisture content between the two slurries is ≤0.5%, the difference in plasticity index is ≤1.5, and the difference in drying linear shrinkage is ≤0.30%. S2. The slurry in the core bearing area and the slurry in the insulating umbrella area are respectively filtered, aged and vacuum kneaded to obtain the mud material in the core bearing area and the mud material in the insulating umbrella area. S3. A composite mud segment is extruded using a coaxial vacuum extrusion die with a core layer flow channel, an annular transition flow channel, and an outer layer flow channel. The core layer flow channel is supplied with mud material for the core area, and the outer layer flow channel is supplied with mud material for the insulating umbrella area. The dry basis mass ratio of the core area mud material to the insulating umbrella area mud material changes in a stepwise manner from the inside to the outside within the annular transition flow channel, thereby obtaining a composite mud segment with a core area, a continuous transition area, and an insulating umbrella area. The coaxial vacuum extrusion die head includes a core layer flow channel, an annular transition flow channel, and an outer layer flow channel arranged coaxially. The core material is extruded through the core layer flow channel, and the insulating umbrella material is extruded through the outer layer flow channel. The annular transition flow channel has 6 to 10 concentric annular distribution channels arranged radially, each channel supplying two types of material in a predetermined ratio. Adjacent material flows undergo shearing and fusion in the co-flow rectification section, causing the mass ratio of the two types of material in the annular transition flow channel to change in a stepwise manner radially. This structure allows for continuous connection with the plasticized material after vacuum kneading, eliminating the need for cold isostatic pressing of large-sized billets. S4. The composite clay segment is subjected to constant moisture settling, pressing and sizing, and spinning to form a suspended porcelain insulator blank. The blank is then subjected to humidity gradient drying, glazing, and firing, so that the temperature difference between the center and the surface of the blank during firing is ≤22℃, thereby obtaining the integrated porcelain part without macroscopic interfaces.

[0012] Preferably, when preparing the slurry for the bearing core area, calcined kaolin, plastic kaolin, potassium feldspar, sodium feldspar, talc, and TiO2 are first wet-milled to D. 50 The particle size is 5.0~7.5 μm. Then, fine-grained α-Al₂O₃, 3Y-ZrO₂ and MgAl₂O₄ spinel seed crystals are added and milled to D. 50 The particle size is 3.5~5.0 μm. Finally, coarse-grained α-Al2O3 is added and mixed at low speed for 20~40 min. When preparing the insulating umbrella area slurry, its base material, 3Y-ZrO2, mullite seed crystals, talc and TiO2 are wet-milled to D. 50 The thickness is 4.0~6.0 μm; the moisture content of the clay material in the bearing core area and the clay material in the insulating umbrella area are both 20.0~22.0%, and the absolute pressure of vacuum clay refining is 2.0~4.0 kPa.

[0013] Preferably, during coaxial vacuum extrusion, the ratio of the average linear velocity at the outlet of the core layer channel to that of the outer layer channel is 0.95:1 to 1.05:1, and the extrusion pressure is 3.5 to 5.5 MPa. The composite mud segment is allowed to stand at a constant humidity of 20 to 25°C and 90 to 96% for 18 to 30 hours. The humidity gradient drying process includes drying at 20 to 25°C and 82 to 90% relative humidity for 30 to 48 hours, drying at 28 to 34°C and 65 to 75% relative humidity for 48 to 72 hours, and drying at 38 to 45°C and 45 to 55% relative humidity for 20 to 36 hours. The residual moisture content of the green body after drying is ≤1.0%.

[0014] Preferably, the firing process includes: raising the temperature from room temperature to 600°C at an average rate of 35-50°C / h, raising the temperature from 600°C to 1050°C at an average rate of 20-30°C / h, raising the temperature from 1050°C to 1260°C at an average rate of 12-18°C / h, raising the temperature from 1260°C to 1295-1315°C at an average rate of 6-10°C / h, and holding at 1295-1315°C for 2.5-4.0 hours; cooling the temperature to 1160-1190°C at a rate of 12-20°C / h and holding for 1.0-2.0 hours, cooling the temperature to 900°C at a rate of 25-40°C / h, cooling the temperature to 400°C at a rate of 40-60°C / h, and cooling the temperature below 400°C with the furnace; during the heating and cooling stages from 1050-1190°C, changing the direction of the circulating airflow inside the kiln every 15-30 minutes.

[0015] Compared with the prior art, the beneficial technical effects of the present invention are as follows: This invention incorporates high-toughness ceramic material containing 3Y-ZrO2, MgAl2O4 spinel seeds, and bimodal α-Al2O3 in the high-stress areas of the head and root of the insulator. Simultaneously, a more easily moldable ceramic material with better dielectric properties is used in the insulating umbrella area, achieving a match between material properties and stress-bearing components. The continuous transition zone eliminates abrupt material interface changes, and through the dual matching of firing linear shrinkage and average linear expansion coefficient, the risk of interface cracking in large-size ceramic components under drying, firing, and alternating loads is reduced. The coaxial vacuum extrusion process can be integrated with existing disc-type suspension ceramic insulator spinning production lines, facilitating stable control of gradient positions and product dimensions, and is suitable for the mass production of 840 kN large-size ceramic insulators. Detailed Implementation

[0016] Unless otherwise specified, all raw materials are on a dry basis. α-Al2O3 purity ≥ 99.5 wt%; calcination temperature of calcined kaolin is 1050℃; Y2O3 content in 3Y-ZrO2 is 3.2 mol%; purity of both MgAl2O4 spinel seed crystals and mullite seed crystals is ≥ 98 wt%.

[0017] The linear shrinkage rate was determined by firing the test strips under the same firing conditions as the product. The average coefficient of linear expansion was determined using a dilatometer at 25–600℃. The three-point bending test specimens were 4 mm × 6 mm × 50 mm in size, with a span of 40 mm and a loading rate of 0.5 mm / min. The fracture toughness was determined using the single-sided pre-splitting beam method. The power frequency breakdown field strength was determined using a 3 mm thick glazed disc in insulating oil. The shear strength in the continuous transition zone was determined using a 6 mm diameter micropillar push-shear specimen. The electromechanical failure load test of the finished product was conducted in accordance with GB / T 1001.1—2021, with 12 insulators used in each group.

[0018] Example 1 The ceramic part has a head height of 106 mm, a head outer diameter of 126 mm, an inner hole diameter of 80 mm, a maximum umbrella diameter of 420 mm, a structural height of 300 mm, and a nominal creepage distance of 700 mm; the radial boundary radius of the load-bearing core area is 94 mm, and the width of the continuous transition zone is 12 mm.

[0019] The core material consists of 49 parts α-Al₂O₃, 19 parts calcined kaolin, 16 parts plastic kaolin, 9 parts potassium feldspar, and 7 parts sodium feldspar. For every 100 parts of the core material, 1.6 parts 3Y-ZrO₂, 1.0 parts MgAl₂O₄ spinel seed crystals, 0.4 parts talc, and 0.25 parts TiO₂ are added. The 49 parts α-Al₂O₃ are composed of 35 parts D... 50 Fine-grained α-Al₂O₃ with a particle size of 1.2 μm and 14 parts of D 50 It consists of coarse-grained α-Al2O3 with a particle size of 6.5 μm.

[0020] The insulating umbrella area base material consists of 39 parts α-Al2O3, 23 parts calcined kaolin, 20 parts plastic kaolin, 11 parts potassium feldspar and 7 parts sodium feldspar; for every 100 parts of the insulating umbrella area base material, 0.30 parts 3Y-ZrO2, 1.4 parts mullite seed crystals, 0.35 parts talc and 0.20 parts TiO2 are added.

[0021] When preparing the core-bearing slurry, kaolin, feldspar, talc, and TiO2 are first wet-milled to D. 50 The particle size was 6.2 μm. Then, fine-grained α-Al₂O₃, 3Y-ZrO₂, and MgAl₂O₄ spinel seed crystals were added and milled to D. 50 The particle size was 4.2 μm. Finally, coarse-grained α-Al₂O₃ was added and mixed at 60 r / min for 30 min. The raw material in the insulating umbrella zone was wet-milled to D. 50 The thickness was 5.0 μm; the two slurries were filtered, iron removed and pressure filtered respectively to make the moisture content 21.0 wt% and 21.2 wt% respectively, and then vacuum-processed under 3.0 kPa absolute pressure after aging for 24 h.

[0022] The core and insulating umbrella sections of the clay, which have undergone vacuum refining, are fed into a coaxial co-extrusion die. Co-extrusion is performed through a core flow channel, an annular transition flow channel, and an outer flow channel to obtain a composite clay segment with a stepped radial composition. The coaxial vacuum extrusion die extrudes a 460 mm diameter composite clay segment at an extrusion pressure of 4.4 MPa. The annular transition flow channel has eight sets of circumferential distribution holes. The dry basis mass ratios of the two clay materials, from the inside out, are 85:15, 75:25, 65:35, 55:45, 45:55, 35:65, 25:75, and 15:85.

[0023] The composite clay segments were allowed to stand at 23℃ and 93% relative humidity for 24 hours. After being pressed, sized, and shaped, they were dried sequentially at 23℃ and 86% relative humidity for 40 hours, at 31℃ and 70% relative humidity for 60 hours, and at 42℃ and 50% relative humidity for 28 hours. The residual moisture content after drying was 0.82 wt%.

[0024] The billet is heated from room temperature to 600℃ at 42℃ / h, then to 1050℃ at 25℃ / h, then to 1260℃ at 15℃ / h, and finally to 1305℃ at 8℃ / h and held for 3.2 h. It is then cooled to 1175℃ at 16℃ / h and held for 1.5 h, before being cooled back to room temperature. Within the temperature range of 1050~1190℃, the direction of the circulating airflow inside the kiln is changed every 20 minutes.

[0025] The plasticity indices of the core material and the insulating umbrella material were 17.1 and 17.7, respectively, and the drying linear shrinkage rates were 4.62% and 4.47%, respectively. (The last part, "10 s," appears to be a separate, unrelated sentence fragment and is left untranslated.) -1 The apparent viscosity measured at the shear rate was 1.08 × 10⁻⁶. 5 Pa·s and 1.03×10 5 Pa·s. The ratio of the average linear velocity at the outlet of the two clay materials was 1.02:1. The maximum temperature difference between the center and surface of the green body during firing, measured using green bodies of the same size, was 18℃.

[0026] The shrinkage rates of the fired core area and the insulating umbrella area were 11.08% and 10.94%, respectively, with a difference of 0.14%; the average coefficients of linear expansion were 6.28 × 10⁻⁶. -6 K -1 and 6.47×10 -6 K -1 The difference is 0.19 × 10 -6 K -1 The width of the continuous transition zone was 11.6 mm, and the maximum variation in 3Y-ZrO2 content between adjacent 1 mm positions was 0.13 wt%. No continuous layered pores were found.

[0027] The three-point bending strength of the load-bearing core region is 318 MPa, and the fracture toughness is 4.48 MPa·m. 1 / 2 The power frequency breakdown field strength in the insulating umbrella region is 34.1 kV / mm, and the volume resistivity is 1.8×10¹³ Ω·m; the shear strength in the continuous transition region is 68 MPa.

[0028] The electromechanical failure loads of the 12 finished insulators ranged from 876 to 936 kN, with an average of 907 kN and a standard deviation of 18 kN. The failure modes were all steel leg pull-out or porcelain head failure. During the test, none of the specimens experienced breakdown or mechanical failure before reaching 840 kN. All three fatigue specimens completed 1×10⁻⁶ kN of fatigue resistance. 6 No new cracks were detected after one alternating tensile cycle.

[0029] Example 2 The difference from Example 1 is that the core material consists of 51 parts α-Al₂O₃, 18 parts calcined kaolin, 15 parts plastic kaolin, 10 parts potassium feldspar, and 6 parts sodium feldspar; 2.0 parts 3Y-ZrO₂ and 1.3 parts MgAl₂O₄ spinel seed crystals are added per 100 parts of the core material; the radial boundary radius of the core is 100 mm, and the width of the continuous transition zone is 14 mm. The fracture toughness of the core is 4.71 MPa·m. 1 / 2 The minimum electromechanical failure load for 12 finished products is 889 kN.

[0030] Example 3 The difference from Example 1 is that the core material consists of 47 parts α-Al₂O₃, 21 parts calcined kaolin, 18 parts plastic kaolin, 8 parts potassium feldspar, and 6 parts sodium feldspar; 1.2 parts 3Y-ZrO₂ and 0.7 parts MgAl₂O₄ spinel seed crystals are added per 100 parts of the core material; the radial boundary radius of the core is 88 mm, and the width of the continuous transition zone is 8 mm. The fracture toughness of the core is 4.08 MPa·m. 1 / 2 The minimum electromechanical failure load for 12 finished products is 858 kN.

[0031] Example 4 The difference from Example 1 is that the insulating umbrella area base material consists of 37 parts α-Al2O3, 25 parts calcined kaolin, 22 parts plastic kaolin, 10 parts potassium feldspar, and 6 parts sodium feldspar; 0.15 parts 3Y-ZrO2 and 1.8 parts mullite seed crystals are added per 100 parts of the insulating umbrella area base material. The power frequency breakdown field strength of the insulating umbrella area is 35.0 kV / mm, and the minimum electromechanical failure load of 12 finished products is 866 kN.

[0032] Example 5 The difference from Example 1 is that the insulating umbrella zone base material consists of 41 parts α-Al2O3, 21 parts calcined kaolin, 18 parts plastic kaolin, 13 parts potassium feldspar, and 7 parts sodium feldspar; 0.45 parts 3Y-ZrO2 and 1.0 parts mullite seed crystals are added per 100 parts of the insulating umbrella zone base material; the width of the continuous transition zone is 16 mm, and the mass ratio of the two materials is continuously adjusted according to an S-shaped curve. The power frequency breakdown field strength of the insulating umbrella zone is 32.6 kV / mm, the shear strength of the continuous transition zone is 72 MPa, and the minimum electromechanical failure load of 12 finished products is 881 kN.

[0033] Comparative Example 1 The difference from Example 1 is that the entire ceramic component uses the insulating umbrella area material of Example 1, without a load-bearing core area or a continuous transition area. The fracture toughness of the head material is 3.12 MPa·m. 1 / 2 The minimum electromechanical failure load of the 12 finished products was 797 kN, of which 7 did not reach 840 kN, and all of them showed microcracks at the head during fatigue testing.

[0034] Comparative Example 2 The difference from Example 1 is that the material of the load-bearing core area and the material of the insulating umbrella area are directly connected at a radius of 100 mm, without a continuous transition zone. After burning, a layered pore of 0.3~1.8 mm is formed at the abrupt interface, and the shear strength of the abrupt joint zone is 31 MPa; 4 out of 12 finished products cracked along the abrupt interface, and the average electromechanical failure load was 804 kN.

[0035] Comparative Example 3 The difference from Example 1 is that the linear shrinkage rate and average linear expansion coefficient of the two firing zones were not matched, resulting in a difference of 0.76% in the linear shrinkage rate and a difference of 0.68 × 10⁻⁶ in the average linear expansion coefficient. -6 K -1 Of the 12 ceramic pieces fired, 5 showed visible ring cracks in the continuous transition zone. The shear strength of the continuous transition zone of the qualified ceramic pieces was 38 MPa.

[0036] Comparative Example 4 The difference from Example 1 is that no 3Y-ZrO2 and MgAl2O4 spinel seed crystals are added to the core region, and it is supplemented with an equal mass of fine-grained α-Al2O3. The fracture toughness of the core region is reduced to 3.26 MPa·m. 1 / 2 The minimum electromechanical failure load of the 12 finished products was 821 kN, and microcracks appeared at the head of all of them during the fatigue test.

[0037] The above results show that by dividing the materials into the load-bearing core region, the continuous transition region, and the insulating umbrella region, as well as matching the firing shrinkage and thermal expansion, the load-bearing capacity and fatigue reliability of the 840 kN suspension porcelain insulator can be improved.

[0038] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A large-tonnage, large-specification 840 kN suspension porcelain insulator, characterized in that, The porcelain component of the suspension porcelain insulator is a dense, integral porcelain component formed by co-firing a load-bearing core area, a continuous transition area, and an insulating umbrella area. With the central axis of the porcelain component as a reference, the load-bearing core area is located at the central head and inside the umbrella root of the porcelain component, the insulating umbrella area is located radially outside the continuous transition area, and the continuous transition area is located between the load-bearing core area and the insulating umbrella area. The raw material systems of the load-bearing core area, the continuous transition area, and the insulating umbrella area do not contain pore-forming agents. The core material of the bearing area, by weight, is composed of the following: 47-51 parts α-Al2O3, 18-21 parts calcined kaolin, 15-18 parts plastic kaolin, 8-11 parts potassium feldspar and 5-8 parts sodium feldspar. Every 100 parts of the carrier core material further includes 1.2 to 2.0 parts of 3Y-ZrO2, 0.7 to 1.3 parts of MgAl2O4 spinel seed crystals, 0.25 to 0.55 parts of talc, and 0.15 to 0.35 parts of TiO2; The insulating umbrella area base material, by weight, comprises the following: 37-41 parts α-Al₂O₃, 21-25 parts calcined kaolin, 18-22 parts plastic kaolin, 10-13 parts potassium feldspar, and 5-8 parts sodium feldspar; each 100 parts of the insulating umbrella area base material further comprises 0.15-0.45 parts 3Y-ZrO₂, 1.0-1.8 parts mullite seed crystals, 0.20-0.50 parts talc, and 0.10-0.30 parts TiO₂. The continuous transition zone is formed by the raw material system of the bearing core region and the raw material system of the insulating umbrella region with a dry basis mass ratio that varies in a stepwise manner along the radial direction. The dry basis mass ratio changes in a stepwise manner from 90:10 to 75:25 near the bearing core region to 25:75 to 10:90 near the insulating umbrella region. The difference in linear shrinkage between the load-bearing core area and the insulating umbrella area under the same firing regime is ≤0.25%, and the difference in the average linear expansion coefficient between 25~600℃ is ≤0.35×10⁻⁶. -6 K -1 .

2. The extra-large tonnage, large-specification 840 kN suspension porcelain insulator according to claim 1, characterized in that, Characterized by the radial variation of 3Y-ZrO2 content, the variation of 3Y-ZrO2 content between adjacent 1 mm positions in the continuous transition zone is ≤0.18wt%, and there are no continuous layered pores with a length greater than 100 μm in the continuous transition zone.

3. The extra-large tonnage, large-specification 840 kN suspension porcelain insulator according to claim 1, characterized in that, The α-Al₂O₃ in the supporting core region is composed of fine-grained α-Al₂O₃ and coarse-grained α-Al₂O₃ with a dry basis mass ratio of 65:35 to 78:

22. The fine-grained α-Al₂O₃ has a D... 50 The Do of the coarse-grained α-Al2O3 is 0.8~1.6 μm. 50 The thickness is 5.0~8.0 μm; the D of the 3Y-ZrO2 50 The diameter is 0.25~0.60 μm; the D of the MgAl2O4 spinel seed crystal is... 50 The range is 0.8~2.0 μm.

4. The extra-large tonnage, large-specification 840 kN suspension porcelain insulator according to claim 1, characterized in that, After firing, the bearing core region comprises 38-48 vol% corundum phase, 16-24 vol% mullite phase, 0.8-1.6 vol% tetragonal ZrO2 phase, and 22-32 vol% glass phase; the insulating umbrella region comprises 28-38 vol% corundum phase, 18-28 vol% mullite phase, and 28-38 vol% glass phase.

5. The extra-large tonnage, large-specification 840 kN suspension porcelain insulator according to claim 1, characterized in that, The porcelain head of the suspension insulator has a height of 100-112 mm, an outer diameter of 120-132 mm, an inner diameter of 74-84 mm, a maximum shed diameter of 410-425 mm, a structural height of 295-305 mm, and a nominal creepage distance of 650-700 mm. The porcelain head, steel cap, and steel foot are glued together to form a disc-shaped suspension porcelain insulator with a specified electromechanical breaking load of 840 kN.

6. A method for preparing an extra-large tonnage, large-specification 840 kN suspension porcelain insulator as described in any one of claims 1 to 5, characterized in that, Includes the following steps: S1. Prepare the slurry for the core area and the insulating umbrella area separately, ensuring that the difference in moisture content between the two slurries is ≤0.5%, the difference in plasticity index is ≤1.5, and the difference in drying linear shrinkage is ≤0.30%. S2. The slurry in the core bearing area and the slurry in the insulating umbrella area are respectively filtered, aged and vacuum kneaded to obtain the mud material in the core bearing area and the mud material in the insulating umbrella area. S3. A composite mud segment is extruded using a coaxial vacuum extrusion die with a core layer flow channel, an annular transition flow channel, and an outer layer flow channel. The core layer flow channel is supplied with mud material for the core area, and the outer layer flow channel is supplied with mud material for the insulating umbrella area. The dry basis mass ratio of the core area mud material to the insulating umbrella area mud material changes in a stepwise manner from the inside to the outside within the annular transition flow channel, thereby obtaining a composite mud segment with a core area, a continuous transition area, and an insulating umbrella area. S4. The composite clay segment is subjected to constant moisture settling, pressing and sizing, and spinning to form a suspended porcelain insulator blank. The blank is then subjected to humidity gradient drying, glazing, and firing, so that the temperature difference between the center and the surface of the blank during firing is ≤22℃, thereby obtaining the integrated porcelain part without macroscopic interfaces.

7. The preparation method according to claim 6, characterized in that, In preparing the slurry for the bearing core region, calcined kaolin, plastic kaolin, potassium feldspar, sodium feldspar, talc, and TiO2 are first wet-milled to D. 50 The particle size is 5.0~7.5 μm. Then, fine-grained α-Al₂O₃, 3Y-ZrO₂ and MgAl₂O₄ spinel seed crystals are added and milled to D. 50 The particle size is 3.5~5.0 μm. Finally, coarse-grained α-Al2O3 is added and mixed at low speed for 20~40 min. When preparing the insulating umbrella area slurry, its base material, 3Y-ZrO2, mullite seed crystals, talc and TiO2 are wet-milled to D. 50 The thickness is 4.0~6.0 μm; the moisture content of the clay material in the bearing core area and the clay material in the insulating umbrella area are both 20.0~22.0%, and the absolute pressure of vacuum clay refining is 2.0~4.0 kPa.

8. The preparation method according to claim 6, characterized in that, During coaxial vacuum extrusion, the ratio of the average linear velocity at the outlet of the core layer channel to that of the outer layer channel is 0.95:1 to 1.05:1, and the extrusion pressure is 3.5 to 5.5 MPa. The composite mud segment is kept at a constant humidity of 20 to 25°C and 90 to 96% for 18 to 30 hours. The humidity gradient drying includes drying at 20 to 25°C and 82 to 90% relative humidity for 30 to 48 hours, drying at 28 to 34°C and 65 to 75% relative humidity for 48 to 72 hours, and drying at 38 to 45°C and 45 to 55% relative humidity for 20 to 36 hours. The residual moisture content of the green body after drying is ≤1.0%.

9. The preparation method according to claim 6, characterized in that, The firing process includes: raising the temperature from room temperature to 600°C at an average rate of 35-50°C / h, raising the temperature from 600°C to 1050°C at an average rate of 20-30°C / h, raising the temperature from 1050°C to 1260°C at an average rate of 12-18°C / h, raising the temperature from 1260°C to 1295-1315°C at an average rate of 6-10°C / h, and holding at 1295-1315°C for 2.5-4.0 h; cooling to 1160-1190°C at a rate of 12-20°C / h and holding for 1.0-2.0 h, cooling to 900°C at a rate of 25-40°C / h, cooling to 400°C at a rate of 40-60°C / h, and cooling with the furnace after the temperature drops below 400°C; during the heating and cooling stages from 1050-1190°C, changing the direction of the circulating airflow inside the kiln every 15-30 minutes.